2014
DOI: 10.1111/boj.12232
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trends in Iridaceae: new cytogenetic findings from the New World

Abstract: With the present work, we aim to provide a better understanding of chromosome evolutionary trends among southern Brazilian species of Iridoideae. Chromosome numbers and genome sizes were determined for 21 and 22 species belonging to eight genera of Tigridieae and two genera of Trimezieae, respectively. The chromosome numbers of nine species belonging to five genera are reported here for the first time. Analyses of meiotic behaviour, tetrad normality and pollen viability in 14 species revealed regular meiosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
3
25
1
Order By: Relevance
“…However, the diploid record is associated with plants characterized as H. aff. lahue by Goldblatt and Takei (1997), and notwithstanding extensive search for diploid plants of H. lahue, the current research recently confirmed the only occurrence of hexaploids (2n = 6x = 42) and octoploids (2n = 8x = 56) in southern Brazil (Moraes et al 2015).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the diploid record is associated with plants characterized as H. aff. lahue by Goldblatt and Takei (1997), and notwithstanding extensive search for diploid plants of H. lahue, the current research recently confirmed the only occurrence of hexaploids (2n = 6x = 42) and octoploids (2n = 8x = 56) in southern Brazil (Moraes et al 2015).…”
Section: Introductionsupporting
confidence: 71%
“…Sampled populations of H. lahue were the same as previously characterized cytogenetically by Moraes et al (2015) ( Table 1). Drawing on cytogenetic characterization, cytotypes were identified preliminarily based on three floral criteria: (A) presence or absence of an uncinate apex in the outer tepals, (B) presence or absence of a constriction in the base from outer tepals, and (C) shape of inner tepals.…”
Section: Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hypotheses have been proposed regarding the importance of fusion and fission in karyotype evolution: whereas some authors claim fusion as the most important type of rearrangement, since truly telocentric chromosomes either do not exist or are very rare [12]; others have suggested centric fission as the main process, as it minimizes the genetic risks due to deleterious reciprocal translocations, as postulated by the Minimal Interaction Theory [1315]. So far, these hypotheses have rarely been tested in a phylogenetic framework (but see [11, 16]).…”
Section: Introductionmentioning
confidence: 99%
“…However, statistical approaches, as ancestral state reconstruction based on maximum likelihood, have recently been applied to infer karyotype evolution in a phylogenetic framework [11, 16, 2628]. In such approaches, the phylogenetical proposals should present all species with karyotype data available and, when nuclear and chloroplast phylogenetic proposals are conflicting, both should be tested independently to reflect the more robust answer about karyotype evolution.…”
Section: Introductionmentioning
confidence: 99%